Evolution of Youth Protest: Soviet Historiography of Informal Youth Associations in Ukraine - Soroka, Svitlana; Faichuk, Olena (Studia Warmińskie, 2022)
This article presents a historiographical study of the informal youth associations of Soviet society that is relevant to contemporary sociology. Although informal youth associations in the Soviet Union had always existed, their analysis was only possible after the beginning of “perestroika”. The activation of research began in 1986–1988. The peak of sociological research on these youth associations, as well as the development of mechanisms to analyse and point in their direction, occurred in 1989–1991. The authors have described the main areas of activity of informal youth associations, as well as how this problem has been addressed by some researchers.